Chapter Modelação de dados poéticos: uma perspectiva desde os dados abertos e ligados/ The modelling of poetic data: A perspective from linked open data - Malta, Mariana Curado (De Gruyter, 2018)
The contributions gathered in this volume show how digital technologies can be applied to Medieval Studies (Philology, Art, and History) in order to improve our understanding of medieval societies and cultures.